Assessment and sources identification of microplastics, PAHs and OCPs in the Luoyuan Bay, China: Based on multi-statistical analysis. (February 2022) - Peng, Bo; Hossain, Kazi Belayet; Lin, Yan; Zhang, Mingyu; Zheng, Haowen; Yu, Junjie; Meng, Xiangliang; Wang, Jilong; Cui, Yaozong; Wu, Bin; Lou, Linghao; Cai, Minggang
Abstract: Luoyuan Bay is a mariculture influenced water body located in southeastern China. Multi-statistical techniques were applied to 21 sampling locations in the bay to identify the sources of microplastics and other pollutants in the sediment. In microplastics detection, fragment was the most abundant shape (~36%), and rayon was the dominant polymer (~59%). The size of more than 48% of total microplastics observed was less than 200 μm. The study showed that the upper part of Luoyuan Bay was dominated by microplastic pollution, while the lower part of the bay was dominated by persistent organic pollutants (PAHs, OCPs). Mariculture is one of the main sources of pollution in Luoyuan Bay. Apart from mariculture, there were additional sources such as industry, land reclamation, port, and so on; industry and land reclamation were the leading sources of microplastics, while port, industry, and mariculture were the primary sources of PAHs and OCPs. Highlights: Mariculture is the main major source of overall pollutants in Luoyuan Bay. Upper region of Luoyuan Bay was dominated by microplastic pollution. Lower region of the bay was dominated by POPs. Industry and land reclamation probably were the main sources of microplastics. Port, mariculture, and industry could be the main sources of POPs.